A correlational analysis of shuttlecock speed kinematic determinants in the badminton jump smash - King, M.; Towler, H.; Dillon, R.; McErlain-Naylor, S. (Applied Sciences, 2020)
The forehand jump smash is an essential attacking stroke within a badminton player`s repertoire. A key determinate of the stroke`s effectiveness is post-impact shuttlecock speed, and therefore awareness of critical technique factors that impact upon speed is important to players/coaches. Three-dimensional kinematic data of player, racket and shuttlecock were recorded for 18 experienced players performing maximal effort forehand jump smashes. Joint angles and X-factor (transverse plane pelvis-thorax separation) were calculated at key instants: preparation, end of retraction, racket lowest point, turning point and shuttlecock contact. Peak shoulder, elbow, and wrist joint centre linear velocities, phase durations and jump height were also calculated. Correlational analyses were performed with post-impact shuttlecock speed, revealing significant correlations to peak wrist joint centre linear velocity (r = 0.767), acceleration phase duration (r = -0.543), shoulder internal/external rotation angle at shuttlecock contact (r = 0.508) and X-factor at the end of retraction (r = -0.484). Multiple linear regression analysis revealed 43.7% of the variance in shuttlecock speed could be explained by acceleration phase duration and X-factor at the end of retraction, where shorter acceleration phase durations and more negative X-factor at end of retraction caused greater shuttlecock speeds. These results suggest that motions of the proximal segments (shoulder and pelvis-thorax separation) are critical to developing greater distal linear velocities, which subsequently lead to greater post-impact shuttlecock speed.